The Belgian Village, Chicago World's Fair (Geston Bros.)
The visitor entering the Fair at 23rd St. steps into the storied environs of Bruges, Ghent and Antwerp. On every hand are the Castled towers and antique Spires of the Belgian village. On these European streets are seen the familiar milk vendors with their dogcats and the peasant girls in fin brocades.